Definition of Local Diagnostic Reference Levels in a Radiology Department Using a Dose Tracking Software. Issue 1 (10th September 2016) - Ghetti, C.; Ortenzia, O.; Palleri, F.; Sireus, M.
Abstract: Dose optimization in radiological examinations is a mandatory issue: in this study local Diagnostic Reference Levels (lDRLs) for Clinical Mammography (MG), Computed Tomography (CT) and Interventional Cardiac Procedures (ICP) performed in our Radiology Department were established. Using a dose tracking software, we have collected Average Glandular Dose (AGD) for two clinical mammographic units; CTDIvol, Size-Specific Dose Estimate (SSDE), Dose Length Product (DLP) and total DLP (DLPtot ) for five CT scanners; Fluoro Time, Fluoro Dose Area Product (DAP) and total DAP (DAPtot ) for two angiographic systems. Data have been compared with Italian Regulation and with the recent literature. The 75th percentiles of the different dosimetric indices have been calculated. Automated methods of radiation dose data collection allow a fast and detailed analysis of a great amount of data and an easy determination of lDRLs for different radiological procedures.